Role of Foeniculum vulgare oil on the antimicrobial activity of some antibiotics against resistant pathogenic Gram-negative bacteria - Abd El-Mongy, Mahmoud .; Mohamed, Shehab E. Talat; Mabrouk, Mona I.; Mohammed, Abeer Mohammed; Hamza, Hanafy A. (Journal of Biochemistry, Microbiology and Biotechnology, 2017)
In this manuscript, the antimicrobial efficacy of fennel oil alone and combined with antibiotics were studied by the agar diffusion method. Fifty samples from edible food were collected from supermarkets in the El-Giza governorate, Cairo, Egypt. The presence of multi drug resistant bacteria in the edible food is reported. The aim of this work focuses the sensitivity improvement of the most five resistant Gram negative bacterial isolates due to the presence of fennel oil in the agar medium. Isolation was carried out by classical method using a selective medium followed by biochemical tests.Â The results showed that the identified isolates include 50 pathogenic bacteria like Staphylococcus spp. 10 isolates (40%), Micrococcus spp. 1 isolate (4%), E. coli 11 isolates (44%), Citrobacter freundii 1 isolate (4%), Enterobacter species 1 isolate (4%), Enterobacter cloacae 1 isolate (4%) and P. aeruginosa 1 isolate (4%). There are significant improvements in the antimicrobial activity of tetracycline against E. coli isolated from milk due to the fennel oil contained medium. In addition, the sensitivity of Enterobacter spp. to meropenem was significantly increased in the medium containing fennel oil. Furthermore, the sensitivity of E. coli and Enterobacter spp. had significantly decreased to ciprofloxacin in the medium containing fennel oil.